A Resilience Study for Housing Resettlement in Post-Conflict Areas: A Case Study of North Cyprus (Aşağı Maraş, Famagusta) - Elinwa, Ugochukwu K. (My University, 2015)
Resilience has become one of the widely discussed and debated concepts since the past 20 years. The growing rate of conflict has prompted enquiries into the resilience of the housing environment. Usually after a major disaster, there are two key terminologies that could be considered at different periods in time. These terminologies are known as shocks and stressors and are used to describe the short and long term challenges of the housing environment as a result of disasters. The study was carried out in Asagi Maras, an area in Famagusta, North Cyprus and was done to understand the nature of resilience within the study area 40 years after the conflict that brought about a mass displacement and resettlement of people in Cyprus. In this study of resilience, the housing environment is considered as a system constituting of several subsystems (Social, Environmental, Political, Economic subsystems). Two major subsystems (Social and Environmental Subsystems) were focused upon due to limitations influencing other subsystems. Within the environmental subsystem, climatic and physical conditions were considered. This also included an understanding of people’s willingness to accept or pay (WTA & WTP) for innovations for enhancing this subsystem. The social subsystem focused on the use of public spaces and how such public spaces can be enhanced to improve resilience. The results of the study revealed that although people had developed certain coping mechanisms, resilience may still not have been reached within the study area. Because of many loose ends that could lead to a collapse if there is a major shock. Keywords: Housing Resilience, Shocks and Stressors, Subsystems

ÖZ: Elastikiyet son 20 yıldır oldukça kapsamlı tartışılan kavramlardan biridir. Dünyada swosyal ve politik açıdan çatısmalar ve çelişkilerin artması konut/yaşam çevrelerinin elastikiyetinin sorgulanmasına yol açmıştır. Genellikle, büyük felaketlerden sonra farklı zaman aralıkları içinde, iki önemli anahtar terminolojinin öne çıktığı görülür. Bu terminolojiler ‘şok’lar ve ‘stres’ler olarak bilinir ve felakatlerin konut çevrelerinde neden olduğu uzun ve kısa dönem sorunları tanımlamak için kullanılır. Bu çalışma elastikiyet olgusunun doğasını anlamak amacıyla Kuzey Kıbrıs Mağusa’da yer alan Aşağı Maraş bölgesinde, adadaki kitlesel yerdeğiştirme ve yeniden yerleştirmeye neden olan sosyal/politik çatışmadan kırk yıl sonar gerçekleşmiştir. Çalışmada, konut çevresi sosyal, çevresel, politik economik vb. gibi bazı alt sistemlerden oluşuğu gözönüne tartışıldı. Bunlar arasında, diğer alt sistemleri de etkileyen sınırlamalar üzerinden sadece sosyal ve çevresel alt sistemlere yoğunlaşıldı. Çevresel alt sistemler içinde iklimsel ve fiziksel koşullar da ayrıca göz önünde tutuldu. Bu yolla bölge sakinlerinin alt sistemlerin geliştirilmesi ve desteklenmesi konusunda bu alandaki iyileştirme ve geliştirmeleri Kabul Etme ve Ödeme Yapma yönünde ne kadar istekli olduklarını (WTA & WTP) anlamak amaçlandı. Sosyal alt sistemler içinde kamusal alanların kullanımına ve bu alanların elastikiyeti desteklemek için nasıl geliştirilebileceğine odaklanıldı. Ne var ki, çalışmanın sonuçları, bölge sakinlerinin belli başlı mekanizmalar üreterek sorunlarla başa çıkma çabalarına ragmen; başlangıçta üstünkörü çözülmüş bir çok durumdan kaynaklanan belirsiz politik çıkmaza bağlı temel ‘şok’ nedeniyle, bölgede tam bir ‘elastikiyet’ durumuna ulaşılamadığını göstermektedir. Anahtar Kelimeler: Konut Çevrelerinde Çatışma ve Çelişki, Şoklar, Stresler, Konut Çevrelerinde Elastikiyet, Alt sistemler
Doctor of Philosophy in Architecture. Thesis (Ph.D.)--Eastern Mediterranean University, Faculty of Architecture, Dept. of Architecture, 2015. Co-Supervisor: Assoc. Prof. Dr. Türkan Ulusu Uraz and Supervisor: Prof. Dr. Naciye Doratlı.
Keywords: Architecture; City and town life - Aşağı Maraş, Famagusta (Cyprus, North); Sociology, Urban - Famagusta (Cyprus, North); City planning - Famagusta (Cyprus, North); Housing Resilience; Shocks and Stressors; Subsystems